Management of distribution risks and digital transformation of insurance distribution: A regulatory gap in the IDD - Pierpaolo Marano (Risks, 2021)
The Insurance Distribution Directive (IDD) aims to regulate insurance distribution in the EU regardless of distribution channels and means. Although new technologies affect insurance distribution, the IDD does not explicitly regulate this digital transformation. Insurers and intermediaries must comply with detailed business conduct rules that aim to counteract distribution risks. However, the IDD exempts ancillary insurance intermediaries from its scope when they meet certain conditions. The article highlights the regulatory framework on insurance, requiring insurers and intermediaries to address distribution risks, and analyses how this exemption affects the management of distribution risks in online distribution from a legal perspective. The focus on online distribution depends on the scale such distribution can achieve. The consideration of the scale allows for challenging the political choice behind the exemption of ancillary insurance intermediaries, which consists of the principle of proportionality. A regulatory proposal to counteract these adverse effects is to remove the exemption from the IDD rules for ancillary intermediaries in online distribution. Such a proposal is compliant with the principle of technological neutrality and is in line with the new legislative proposals in the Digital Services Act and Digital Markets Act.
Keywords: 330; digital transformation; distribution risks; insurance distribution; Insurance Distribution Directive; insurance distributors; principle of proportionality; principle of technological neutrality; product governance